Pengaruh Return on Assets Dan Debt to Equity Ratio Terhadap Pertumbuhan Laba Pada Perusahaan Sektor Healthcare Terdaftar Di BEI : The Effect of Return on Assets and Debt to Equity Ratio on Profit Growth in Healthcare Sector Companies Listed on the IDX - Diffa Miftaah Huljannah; Nurul Aisah; Chodidjah (Jurnal Manajemen dan Akuntansi Cakrawarti, 2026)
Profit growth is one of the indicators used to assess a company's financial performance because it reflects the company's ability to improve finances from the previous period to the next. The purpose of this study is to analyze the effect of Return on Assets and Debt to Equity Ratio on Profit Growth in Healthcare Sector Companies listed on the IDX. This research method uses a statistical quantitative method with secondary data in the form of financial reports obtained from the company's official website or the official IDX website. The sampling technique in this study uses purposive sampling while data indicated as outliers are excluded to meet the research assumptions. The research findings show that Return on Assets has an effect on profit growth with t count 6.334 > 2.016 with sig. 0.000 < 0.05, Debt to Equity Ratio has an effect on profit growth with t count 4.360 > 2.016 with sig. 0.000 > 0.05. Return on Assets and Debt to Equity Ratio simultaneously influence profit growth with F count 20.989 > 4.067, with sig. 0.000 < 0.05.